PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DALAM PERSPEKTIF PENDIDIKAN NILAI DI SMP N 4 BOYOLALI - Yoga Wicaksono; Joko Subando (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
This paper examines the development of the Islamic education curriculum from the perspective of values education at SMP N 4 Boyolali. The aim is to improve the quality of Islamic education and the religious values instilled in students. The study uses a descriptive qualitative method and collects data through interviews, observations, and documentation. The results suggest that SMP N 4 Boyolali's Islamic religious education curriculum has not effectively conveyed the intended religious values to students. Therefore, developing the Islamic education curriculum from a values education perspective is necessary to improve the quality of Islamic education and achieve the desired educational goals. The data were analyzed using the descriptive analysis developed by Miles and Huberman, which yielded findings on the development of the Islamic education curriculum from a values education perspective.